From women's empowerment to food security: revisiting global discourses through a cross-country analysis - Clement, Floriane; Buisson, Marie-Charlotte; Leder, Stephanie; Balasubramanya, Soumya; Saikia, Panchali; Bastakoti, Ram C.; Karki, Emma; van Koppen, Barbara (Elsevier, 2019)
Global discourses have advocated women's empowerment as a means to enhance food security. Our objective was to critically review the causal linkages between women's empowerment and food availability and access. We relied on mixed methods and a cross-country analysis, using household survey data from Bangladesh, Nepal and Tajikistan and qualitative data from Nepal. The quantitative analysis highlights the diversity of patterns linking empowerment and food security indicators and the roles socio-economic determinants play in shaping these patterns across countries. The qualitative analysis further stresses the need for a truly intersectional approach in food security programmes that supports challenging the structural barriers that keep marginalised men and women food insecure. Lastly, our findings call for informing standardised measures of empowerment with an assessment of local meanings and values.